2022
DOI: 10.1097/rhu.0000000000001871
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of SARS-CoV-2 Vaccination in Patients With Rheumatic Diseases: A Systematic Review and Meta-analysis

Abstract: Background: Patients with rheumatic disease (RD) are at increased risk for COVID-19 infection. Large clinical trials have demonstrated efficacy and safety of SARS-CoV-2 vaccine. However, patients with RD are typically excluded from these trials. Objective:The aim of this study was to conduct a systematic review and meta-analysis examining the immunogenicity and safety of SARS-CoV-2 vaccination in patients with RD. Methods:We systematically searched PubMed/MEDLINE and Scopus to identify observational studies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
1
5
1
1
Order By: Relevance
“…As most of the included studies investigated immune responses in psoriasis patients, this is consistent with our findings that the pooled seroconversion rate was comparable between groups. However, this result is somewhat contradictory to previous studies conducted in immune-mediated inflammatory disease and inflammatory bowel disease patients, where inferior immunological responses were demonstrated ( 12 , 15 , 38 40 ). This may be due to more aggressive treatment regimens for immune-mediated diseases of other organs compared with the skin.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As most of the included studies investigated immune responses in psoriasis patients, this is consistent with our findings that the pooled seroconversion rate was comparable between groups. However, this result is somewhat contradictory to previous studies conducted in immune-mediated inflammatory disease and inflammatory bowel disease patients, where inferior immunological responses were demonstrated ( 12 , 15 , 38 40 ). This may be due to more aggressive treatment regimens for immune-mediated diseases of other organs compared with the skin.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results also showed that IMDD patients receiving immunosuppressive drugs had a lower anti-SARS-CoV-2 IgG level than HCs. This is consistent with prior studies of immunosuppressed patients taking rituximab, mycophenolate, azathioprine, and glucocorticoids ( 15 , 16 , 38 ). However, one should be cautious that the same medications may not exert the same degree of immunosuppression in different diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Initial studies on this topic have shown a strong dependence of the vaccination response on the underlying DMARD therapy [3]. Glucocorticoids, mycophenolate, abatacept, and especially rituximab seem to be associated with a particularly strong attenuation of the humoral response [4].…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-seven percent of SOTRs with antimetabolites (mycophenolic acid or azathioprine) had negative antibody response after two doses of mRNA vaccine compared to 18% of those without antimetabolites [ 2 ]. A recent meta-analysis in patients with rheumatic diseases revealed that using MPA reduced the rate of seroconversion after SARS-CoV-2 vaccination by 44% [ 22 ].…”
Section: Discussionmentioning
confidence: 99%